Complications following frenotomy for ankyloglossia: A 24‐month prospective New Zealand Paediatric Surveillance Unit study. (12th November 2019) - Hale, Matthew; Mills, Nikki; Edmonds, Liza; Dawes, Patrick; Dickson, Nigel; Barker, David; Wheeler, Benjamin J
Abstract : Aim: To investigate the incidence and characteristics of complications arising from frenotomy for ankyloglossia (tongue‐tie) in New Zealand. Methods: Prospective surveillance among hospital‐based paediatricians of complications arising from frenotomy for ankyloglossia to children <1 year old was conducted by the New Zealand Paediatric Surveillance Unit for 24 months, from August 2016 to July 2018, inclusive. Results: A total of 16 cases of complications arising from frenotomy were reported. The overall average annual incidence rate was 13.9/100 000. Geographic variation was noted with a peak of 85.6/100 000 in one region. Complications reported: poor feeding (44%), respiratory events (25%), pain (19%), bleeding (19%) and weight loss (19%). Three children (19%) also had delayed diagnosis of an underlying medical condition initially overlooked in favour of treating their ankyloglossia, this has not previously been reported. The majority (75%) of cases required admission to hospital. Treatments given included supplementary feeds (44%), surgical intervention (25%), breastfeeding support (19%), analgesia (13%) and blood products (13%). A total of 25% of children had one or more frenotomies; 50% were treated for two or more of: 'anterior' ankyloglossia, 'posterior' ankyloglossia or 'lip tie'; 50% had their frenotomies performed out of the hospital. Dentists were the most common performing practitioner (31%). Conclusions: Frenotomy rates in New Zealand are unknown. Poor feeding, pain, bleeding, weight loss and delayed diagnosis of an alternative underlying medical condition are important complications that require hospital assessment and admission. Practitioners and parents/families need to be aware of these possibilities. Centralised guidelines with access to specialist second opinions should be developed.